Development and validation of the Reception Protocol and Didactic-Pedagogical Guidelines to assist students with Visual Impairments (Research, Society and Development, 2022)
With the evolution of legislation regarding people with disabilities, the inclusion of students with visual impairments in higher education has been widely discussed. Despite the advances made, it still faces important barriers such as the lack of training and the insecurity of teachers to work with these students, negatively impacting their entry into the world of work. Based on these considerations, this article aims to develop and validate a Welcoming Protocol and didactic-pedagogical guidelines for serving visually impaired students, promoting the approximation of the teacher and the student. The methodology is characterized by an evaluative, methodological study, centered on specialists, using criteria for the construction of the protocol and content validation. For the validation, two instruments called Feedback 1 and Feedback 2 were developed, which were answered by the specialists and analyzed by calculating the content validation index, agreement test and descriptive statistical analysis. After the analyzes, the protocol was validated, so the final version can be used by teachers to identify which pedagogical didactic procedures should be chosen to better serve the visually impaired student, thus contributing to the teaching-learning process and to professional training of this population.